A high-resolution temporal record of environmental changes in the Eastern Caribbean (Guadeloupe) from 40 to 10 ka BP. (1st January 2017) - Royer, Aurélien; Malaizé, Bruno; Lécuyer, Christophe; Queffelec, Alain; Charlier, Karine; Caley, Thibaut; Lenoble, Arnaud
Abstract: In neotropical regions, fossil bat guano accumulated over time as laminated layers in caves, hence providing a high-resolution temporal record of terrestrial environmental changes. Additionally, cave settings have the property to preserve such organic sediments from processes triggered by winds (deflation, abrasion and sandblasting) and intense rainfall (leaching away). This study reports both stable carbon and nitrogen isotope compositions of frugivorous bat guano deposited in a well-preserved stratigraphic succession of Blanchard Cave on Marie-Galante, Guadeloupe. These isotopic data are discussed with regard to climate changes and its specific impact on Eastern Caribbean vegetation during the Late Pleistocene from 40 to 10 ka cal. BP. Guano δ 13 C values are higher than modern ones, suggesting noticeable vegetation changes. This provides also evidence for overall drier environmental conditions during the Pleistocene compared to today. Meanwhile, within this generally drier climate, shifts between wetter and drier conditions can be observed. Large temporal amplitudes in both δ 13 C and δ 15 N variations reaching up to 5.9‰ and 16.8‰, respectively, also indicate these oceanic tropical environments have been highly sensitive to regional or global climatic forcing. Stable isotope compositions of bat guano deposited from 40 to 35 ka BP, the Last Glacial Maximum and the Younger-Dryas reveal relatively wet environmental conditions whereas, at least from the end of the Heinrich event 1 and the Bølling period the region experienced drier environmental conditions. Nevertheless, when considering uncertainties in the model age, the isotopic record of Blanchard Cave show relatively similar variations with known proxy records from the northern South America and Central America, suggesting thus that the Blanchard Cave record is a robust proxy of past ITCZ migration. Teleconnections through global atmospheric pattern suggest that islands of the eastern Caribbean Basin could be also under the influence of a bipolar temperature gradients that impact the mean location of the ITCZ, with a Southern Hemisphere imprint during the glacial period and a more significant role of Northern Hemisphere during the last deglaciation. Highlights: Fossil bat guano from Blanchard Cave provide a high-resolution terrestrial record. Relatively wet conditions prevailed during MIS 3 and the beginning of MIS 2. The Upper Pleistocene arid maximum is a brief period ranging from ca 16 to 13 ka BP. Blanchard Cave record is a robust proxy of past ITCZ migration. Eastern Caribbean Basin was under the influence of a bipolar temperature gradients.